Magnetic properties of spinels CoxZn1−xCr2O4 systems: Green's functions, high-temperature series expansions technique and mean-field theory. (3rd April 2021) - El Grini, A.; Masrour, R.; Jabar, A.; Salmi, S.; Azouaoui, A.; El Haoua, M.; Bouslykhane, K.; Hourmatallah, A.; Hamedoun, M.; Benzakour, N.; Rezzouk, A.; Kharbach, J.
ABSTRACT: Many-body Green's function and mean-field theories have been developed for magnetic systems Co x Zn1− x Cr2 O4 . We apply these theories to evaluate the thermal magnetization and magnetic susceptibility for different values of magnetic field and dilution x, by considering all components of the magnetization when an external magnetic field is applied in ( x - z ) plane. The critical temperature of Co x Zn1− x Cr2 O4 spinels have been calculated in the range 0 ≤ x ≤ 1. The Green's function results are compared with the results of high-temperature series expansion technique and experimental magnetic measurements.